Stabilizing sub-2-nm CuIr nanoalloys with cucurbit[6]uril for oxygen evolution reaction in strong acid - You, Hanhui (2024)
Designing applicable high activity over long-term operation Ir-based alloy oxygen evolution reaction (OER) catalysts plays an important role in the development of the water-splitting process under acidic conditions. Herein, we report that cucurbit[6]uril-supported copper-iridium alloy (CB[6]-CuIr) hybrid with the enhancement of activity and stability for OER. The CB[6]-Cu0.33Ir0.67 shows a current density of 11.68 mA/cm2, which is 8.4 times greater than that of Ir black at η = 280 mV. CB[6]-Cu0.33Ir0.67 exhibits superior stability without activity loss after 10 h of continuous operation at 10 mA/cm2, while the CuIr alloy stabilized by carbon or polyvinylpyrrolidone is deactivated within 1 and 4 h, respectively. X-ray absorption fine structure (XAFS) and electron energy loss spectroscopy (EELS) confirm the interaction between the Cu0.33Ir0.67 alloy and CB[6] that can avoid the formation of dissoluble CuIr oxides. This is the first report on using CB[6] to make binary nanoalloys, providing insights into the application of the supramolecules in functionalizing nanomaterials.